"We have been thrown away": surplus people projects and the logics of waste. (4th May 2018) - Wenzel, Jennifer
ABSTRACT: This essay considers discourses of waste that include humans among the objects of discard: surplus/disposable populations in the Marxian tradition, or what Zygmunt Bauman has called "human waste." Notions of "surplus people" have a long history in South Africa, and this essay traces a genealogy of their narrative and cultural forms. These forms can alternately mask and expose the "indispensable dispensab[ility]" of vulnerable communities treated as waste: devastated, depleted, discarded, disregarded. I situate the blockbuster film District 9 within a longer tradition of documenting the plight of people who recognise that they have been "thrown away, " in texts by Solomon T. Plaatje, Cosmas Desmond, Nadine Gordimer, and others. Attending to questions of geographic and temporal scale, I read between the historical example of South African apartheid and "global apartheid" as shorthand for the stratifications effected by neoliberal globalisation. How do these formations attend to the ideological violence, racial specificity, and enforced invisibility of surplus? This exclusion from the polity works through acts of un-imagining: in moments of crisis when they are pushed to the brink, the poor may have no recourse to the ethical and political grounds upon which they might claim the right to survival.